2017
DOI: 10.1021/acsami.7b08733
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Ultrabright SERS Probes with Embedded Reporters for Bioimaging and Photothermal Therapy

Abstract: Plasmonic nanoparticles can be utilized as surface-enhanced Raman scattering (SERS) probes for bioimaging and as photothermal (PT) agents for cancer therapy. Typically, their SERS and PT efficiencies reach maximal values under the on-resonant condition, when the excitation wavelength overlaps the localized surface plasmon resonance (LSPR) wavelength preferably in the near-infrared (NIR) biological window. However, the photogenerated heat may inevitably disturb or even destroy biological samples during the imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 71 publications
4
64
1
Order By: Relevance
“…Transmission electron microscopy (TEM) imaging clearly demonstrates the spherical shape and the core–shell structure of the obtained Au@BDT@Ag NPs, with Ag shell of 11 ± 3 nm in thickness (Figure b,i). From the high resolution TEM image, it is confirmed that there is no distinct gap between the Au core and the Ag shell layer (Figure b,ii), which is consistent with our previous observation on Au@BDT@Ag core–shell rod‐like nanoprobes . The Au@BDT@Ag suspension shows a yellow color and the corresponding LSPR peak blueshifts to 426 nm (Figure c,iii), which further indicates the successful coating of the Ag shell .…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Transmission electron microscopy (TEM) imaging clearly demonstrates the spherical shape and the core–shell structure of the obtained Au@BDT@Ag NPs, with Ag shell of 11 ± 3 nm in thickness (Figure b,i). From the high resolution TEM image, it is confirmed that there is no distinct gap between the Au core and the Ag shell layer (Figure b,ii), which is consistent with our previous observation on Au@BDT@Ag core–shell rod‐like nanoprobes . The Au@BDT@Ag suspension shows a yellow color and the corresponding LSPR peak blueshifts to 426 nm (Figure c,iii), which further indicates the successful coating of the Ag shell .…”
Section: Resultssupporting
confidence: 89%
“…We have additionally observed that a quite uniform nanogap can form inside Au@BDT@ Au NPs if a 1,4-BDT multilayer is embedded into the gap. [67] After careful examination of the literature [27,30,34,71] and our previous results, [38][39][40]63,67] we notice that the absence of clear gaps is a common feature in Au@molecule@Ag NPs with various particle shapes (e.g., nanosphere or nanorod) and embedded reporter molecules (e.g., 1,4-aminothiophenol, 4-mercaptobenzoic acid, cysteamine, and 1,4-BDT). The existence of the nanogap seems greatly connected to the metal of the external shell, for example, Au or Ag.…”
Section: Comparison Of Au@bdt@ag and Au@bdt@au Npsmentioning
confidence: 59%
See 1 more Smart Citation
“…28 This important feature has been conrmed before by the high-resolution TEM but without a clear explanation yet. 28,34 The corresponding high-resolution inverted TEM images of GERTs are shown in the insets of Fig. 1a, which further conrm the observation of the gap morphology above.…”
Section: Resultsmentioning
confidence: 93%
“…We have synthesized ve different types of GERTs, either with different embedded Raman reporter molecules, shell thicknesses, or nanoparticle (NP) shapes using the slightly modied procedures we described before. 22,28 Fig. 1a shows the schematic illustration of GERTs and the corresponding molecular structures of embedded Raman reporters:…”
Section: Resultsmentioning
confidence: 99%